Analisis Pendapatan Usaha Ternak Ayam Ras Petelur di Langngottong Tajuddin Farm Kecamatan Baula Kabupaten Kolaka - Abadi, Musram; Azhari, Sri Ayu; Libriani, Restu (Universitas Muhammadiyah Kotabumi, 2025)
This study aims to analyze (1) the business profile of layer breed chicken farm in Langngottong Tajuddin Farm, Baula District, Kolaka Regency, (2) analyze the income of layer breed chicken farm in Langngottong Tajuddin Farm, Baula District, Kolaka Regency and (3) determine the feasibility of Langngottong Tajuddin Farm layer breed chicken farm based on R/C and B/C analysis. The location of this research was Langngottong Tajuddin Farm, Baula District, Kolaka Regency. Purposive sampling was used to select the location. Data collection is done by observation, conducting interviews and documentation. The data sources used are primary and secondary data. The analysis method used is income analysis, R/C ratio analysis and B/C ratio analysis. The results showed that the income obtained by Langngottong Tajuddin Farm's livestock business amounted to Rp743,819,333 per period. R/C Ratio value of 1.07 or > 1, then the business is feasible to run. While the B / C Ratio value is 0.07 or> 0, then the business is feasible to run.